The Use of Digital Tools to English Learn Vocabulary Among 6th Semester English Language Education Students at the University of Mataram - Ariani, Farika Dwi; Soepriyanti, Henny; Melani, Boniesta Zulandha; Kamaluddin (Journal of Authentic Research, 2026)
English vocabulary mastery has undergone significant changes with the emergence of digital technology. This study aims to examine the use of digital tools in English vocabulary learning by students in the English Language Education Study Program at the University of Mataram, focusing on the utilization of various digital tools. This study used a descriptive qualitative design. Data were collected through online questionnaires completed by 52 participants and in-depth interviews with 10 purposively selected participants. Data were analyzed using thematic analysis based on the Braun and Clarke (2006) model. The results show that students use various digital tools in an integrated manner, combining social media, learning applications, digital dictionaries, and artificial intelligence (AI) in the vocabulary learning process. This process occurs continuously through the stages of discovering new words, understanding their meanings, and using them in sentences or conversations. Furthermore, the effectiveness of digital materials is evident in the multimodal support provided, such as visual and auditory aids to support understanding of meaning and pronunciation. The study also identified barriers to the use of digital tools, including distractions from non-educational content and technical issues related to internet connection. These findings indicate that the functional effectiveness of digital learning tools is directly related to students' strategies and their independent learning abilities. Theoretical and practical implications for the development of technology-based vocabulary learning are also discussed.